Features of determination banking in the legislation of Ukraine - Глібко, С. В. (Theory and practice of jurisprudence, 2016)
The effect of financial intermediation on legislative regulation of banking activities and in determining the content of economic and legal regulation, explored the issue of grounds grouping of banking operations and their relationship with financial services.